New U-Pb (zircon) age and geochemistry of the Wedgeport pluton, Meguma terrane, Nova Scotia - MacLean, Natalie; Barr, Sandra; White, Chris; Ketchum, John (Atlantic Geology, 2003)
ABSTRACT A new U-Pb (zircon) age of 357 ±1 Ma for the Wedgeport pluton in the Meguma terrane of southwestern Nova Scotia conﬁrms that it is younger than other granitoid plutons of the Meguma terrane but not as young as the ca. 316 Ma age based on previous geochronological work. The pluton consists of mainly homogeneous biotite monzogranite characterized by abundant accessory phases including garnet, zircon, epidote, titanite, and ilmenite. Major minerals are quartz, plagioclase (albite-oligoclase), and perthitic microcline. The pluton has consistently high SiO2 content (average ca. 75%) but shows some internal variation consistent with fractional crystallization of feldspar and biotite, together with accessory phases such as zircon. Tectonic setting during emplacement of the pluton was likely within plate, but classiﬁcation is ambiguous because the pluton has characteristics of all three granite types. Peraluminous composition and presence of ilmenite and aluminous minerals such as Fe-rich biotite and garnet suggest S-type afﬁnity, but other characteristics such as high-level emplacement, accessory ﬂuorite, and some chemical characteristics (high Ga/Al ratio, elevated Nb and Y) indicate A-type afﬁnity, whereas abundant titanite and overall chemical character is compatible with felsic I-type composition. The granite has specialized characteristics such as elevated Rb relative to Sr and Ba, and high U and Th compared to all of the average granite types. High εNd values (+2 to+3) indicate a relatively primitive source compared to other plutons of the Meguma terrane. The Wedgeport pluton appears to be unique in the Meguma terrane in both age and composition, although similar plutons may occur in inboard terranes of the Appalachian orogen.